Developing the archaebacteria and eubacteria web-based learning media for high school students - Maulida Ulfa Hidayah; Sonja V. T. Lumowa; Didimus Tanah Boleng (JPBI (Jurnal Pendidikan Biologi Indonesia), 2018)
The 21st-century biology learning requires technology-based learning which is potential in improving students’ learning outcomes. This research aimed to examine the validity and effectiveness of web-based learning media on Archaebacteria and Eubacteria on learning process. This web-based learning media was structured by using 4-D Thiagarajan model. The research was conducted at three SSHSs of Samarinda. The data were obtained from validators’ (media expert, material expert, and linguist), teachers’, and students’ opinion by using questionnaire; while the effectiveness was determined based on students’ test score and their response. The results showed that the web-based learning media was very valid with the average score from experts as high as 95.27%. Moreover, this media has been proven to improve the student’s cognitive learning outcomes (gain score 0.39) and well responded by both teachers and students.